ASESMEN PERKEMBANGAN SOSIAL-EMOSIONAL ANAK USIA DINI DALAM PEMBELAJARAN: STUDI LITERATUR TERKINI - Yuliana, Yuliana; Aslamiah, Aslamiah (SINERGI : Jurnal Riset Ilmiah, 2025)
The social-emotional development of early childhood is crucial for the success of social interactions and future learning readiness. This study systematically examines social-emotional assessment methods in early childhood education using the Systematic Literature Review (SLR) approach. The research analyzes scientific articles published between 2020–2025 and books published between 2015–2025. The findings reveal that direct observation, anecdotal records, interactive digital media, and developmental checklists are commonly used to assess social-emotional development. The results also highlight the importance of fostering children’s empathy, emotional regulation, and social skills. This study supports the selection of appropriate and contextual assessment techniques. It also emphasizes the importance of teacher training in implementing holistic and authentic social-emotional assessments. This review is expected to enhance assessment practices in early childhood education and serve as a reference for policymaking in the field.